Outline of a critique of the fetishist understanding of the formation of the state of Espírito Santo as “economic formation” - Evangelista de Andrade, Luiz Antônio (Geografares, 2020)
In the last 40 years, a extensive collection of researches related to the theme of “economic formation” of Espirito Santo have been formed, which, through of category of modernization, contributed to consolidate an interpretation about process of development of Espirito Santo that treated it of positive way not only in the academic understanding about “economic formation”, but also on common sense. Assuming that this positivation reaffirms the fetishist character this category and the thematic in question, our goal was to identify the approaches that support them and propose a new theoretical contribution to understanding it, based on critical of dissociation-value. This identification was made in two studies of Economic History elaborated by Gabriel Bittencourt, a teacher and researcher that was part of the History Department of Federal University of Espirito Santo
Keywords: Modernization of Espirito Santo, Brazil; Fetishism; Economic Formation Espirito Santo, Brazil